Lessons From My 30 Years of Snakebite Management (Indian Journal of Public Health Research & Development, 2026)
Inspite of various guidelines for snakebite management, in real life, every case of snakebite poses a unique challengeand one may not always be able to abide strictly by the guidelines. There are a just a handful of physicians whoare experts in managing snakebite. This article has been written by Dr D C Patel in Dharampur, Gujarat who hasbeen treating snakebite victims for more than 30 years. This short communication draws on over three decadesof clinical data and practice-based insights, offering guidance for public health professionals and communitymedicine practitioners in remote, resource-constrained settings.Data from April 1993 to March 2024 has been presented along with tips on snakebite management. His analysispresents a few insights- Russell’s viper bites have increased steeply over the years in Dharampur area and Valsaddistrict of Gujarat. The mean number of vials used to manage bites by various species have fallen over time.Regular public awareness programshave borne fruit. Fewer patients visit faith healers and they reach the hospitalquickly. Management of cases using the syndromic approach, early and adequate administration of clinicallyestimated amount of AVS along with organ support is the essential triad of management.
Keywords: Russell’s viper, Saw scaled viper, Cobra, Krait, envenomation, haemotoxic, neurotoxic, anti-snake venom serum.